2015
DOI: 10.1073/pnas.1417207112
|View full text |Cite
|
Sign up to set email alerts
|

Rab3-interacting molecules 2α and 2β promote the abundance of voltage-gated Ca V 1.3 Ca 2+ channels at hair cell active zones

Abstract: Ca2+ influx triggers the fusion of synaptic vesicles at the presynaptic active zone (AZ). Here we demonstrate a role of Ras-related in brain 3 (Rab3)-interacting molecules 2α and β (RIM2α and RIM2β) in clustering voltage-gated Ca V 1.3 Ca 2+ channels at the AZs of sensory inner hair cells (IHCs). We show that IHCs of hearing mice express mainly RIM2α, but also RIM2β and RIM3γ, which all localize to the AZs, as shown by immunofluorescence microscopy. Immunohistochemistry, patch-clamp, fluctuation analysis, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
169
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 73 publications
(191 citation statements)
references
References 61 publications
(87 reference statements)
7
169
0
1
Order By: Relevance
“…The Ca 2+ -channel complex at IHC AZs is likely composed of splice variants of the pore-forming subunit Ca V 1.3α containing exons 43S or 43L (36), of the Ca V β2 (33), and less likely of other Ca V β subunits (32), and of a yet-to-be-identified Ca V α2δ subunit. Ca V β2, the synaptic ribbon, and the presynaptic scaffolds bassoon and RIM2α and β were previously shown to promote the abundance of Ca V 1.3 at IHC AZs (15,33,43), whereas harmonin seems to reduce the number of synaptic Ca V 1.3 (44). Work in zebrafish hair cells has revealed an intriguing molecular interplay between RIBEYE and Ca V 1.3 channels, whereby RIBEYE overexpression promotes the formation of Ca V 1.3-positive AZ-like specializations and synaptic Ca 2+ influx negatively regulates RIBEYE abundance at the AZ (63,64).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The Ca 2+ -channel complex at IHC AZs is likely composed of splice variants of the pore-forming subunit Ca V 1.3α containing exons 43S or 43L (36), of the Ca V β2 (33), and less likely of other Ca V β subunits (32), and of a yet-to-be-identified Ca V α2δ subunit. Ca V β2, the synaptic ribbon, and the presynaptic scaffolds bassoon and RIM2α and β were previously shown to promote the abundance of Ca V 1.3 at IHC AZs (15,33,43), whereas harmonin seems to reduce the number of synaptic Ca V 1.3 (44). Work in zebrafish hair cells has revealed an intriguing molecular interplay between RIBEYE and Ca V 1.3 channels, whereby RIBEYE overexpression promotes the formation of Ca V 1.3-positive AZ-like specializations and synaptic Ca 2+ influx negatively regulates RIBEYE abundance at the AZ (63,64).…”
Section: Discussionmentioning
confidence: 97%
“…Future experiments simultaneously addressing presynaptic properties and postsynaptic firing will be required to further test our hypothesis. -channel subunits and splice variants (33,36,59) as well as by that of scaffold proteins that tether Ca 2+ channels to the AZ (15,42,43,60,61) and/or regulate their turnover (44) by direct or indirect interaction with the channels. Moreover, subunit composition as well as splice variants and interacting proteins also modulate functional properties of the specific Ca 2+ channel (62).…”
Section: Discussionmentioning
confidence: 99%
“…IHC Ca V 1.3 Ca 2+ channels stand out by reason of their hyperpolarized activation range and modest inactivation (10,18,19,22,45). These properties have been attributed to the molecular composition of the native Ca 2+ -channel complexes that, in addition to the specific pore-forming Ca V 1.3α1 splice variant (46), auxiliary Ca V β2 (6,47), and Ca V α 2 δ2 (7) subunit, also contain interactions partners, such as Rab3-interacting molecule (RIM) (48,49); harmonin (50, 51); calmodulin; and, notably, CaBPs (this study and refs. 18,19,34).…”
Section: Discussionmentioning
confidence: 99%
“…The expression of Ca 2þ channels at active zones is partially regulated by the protein RIM in the calyx of Held (Han et al, 2015), RIM isoforms have been found at both calyceal synapses (Dulubova et al, 2005;Mendoza Schulz et al, 2014) and as well as at mature IHC ribbon synapses (Jung et al, 2015). The RIM interactor Rab3 seems to be present at the calyx of Held (Dulubova et al, 2005) and unpublished data (Susann Michanski, G€ ottingen) suggest the presence of Rab3 in IHCs.…”
Section: Similarities and Differences Of The Molecular Composition Ofmentioning
confidence: 92%